Construction And Validation Of Career Interest Scale For Senior Secondary Schools Students In Nigeria - Kolawole, E. B.; Fabunmi, J.I. (Advances in Social Sciences Research Journal, 2014)
The construction and validation of career interest scale is borne out of the need to develop an interest scale that will be valid and reliable for the measurement of interest of any individual student who aspires to choose a direction of study that will enable him perform exceptionally well in any chosen field. The study is directed to the SSII students who are in their penultimate year of writing their final secondary school examination. A total of 1090 responses were processed. A multistage random sampling technique was adopted, and the population was the Senior Secondary Schools in the southwest Nigeria. The construct validity was established by convergent validity of the instrument “Student Career Inventory” (SCIn) with Career Interest Survey (downloaded from internet) and Vocational Interest Inventory developed locally by C.G.M. Bakare (1977) both with correlations of 0.63 and 0.58 respectively. Factor analysis was also employed to further confirm the content, construct, and the unidimentionality of the instrument. It also confirmed the criterion related reliability of the instrument with Holland’s postulations. The result further proved that, apart from validity and reliability of the instrument, it revealed that there was significant difference in the choice of career interest between students in urban and rural locations; and between male and female students in south west Nigeria.